Pendekatan Pengkajian Agama dalam Perspektif Psikologi - Muhammad Akmal Fachrezy; Fasih Wildan Muzakky (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to systematically examine the psychological approach to the study of religion, including its definition, the relationship between psychology and religion, and its application in understanding human religious behavior. This research employs a library research method by collecting and analyzing data from various primary and secondary sources such as books, scientific journals, and relevant previous studies. The findings indicate that the psychological approach to the study of religion focuses on human behavior, inner experiences, and mental conditions without judging the doctrinal truth of any religion. The relationship between psychology and religion is complementary, where religion influences individuals' mental health and psychological well-being, while psychology helps explain the mechanisms of belief formation and the development of religiosity. The application of this approach includes the analysis of religious motivation, understanding of spiritual experiences, the study of religious development across the lifespan, religious coping, and the integration of spirituality into counseling and psychotherapy. In conclusion, the psychological approach makes a significant contribution to understanding religious phenomena empirically and scientifically.